CULTURAL ECOLOGY CHANGE AND SUSTAINABLE DEVELOPMENT: CHALLENGES FOR KAJIAN BUDAYA IN PRAXIS - Butler, Diane (International Conference on Cultural Studies; Vol 1 (2018): Proceedings International Conference on Cultural Studies, 2018)
This essay reflects on the distinct approach of the Balinese school of Kajian Budaya at Universitas Udayana, initiated by the now-late I Gusti Ngurah Bagus, particularly in terms of the topic of cultural ecology change and sustainable development. It draws from my years of work as a dance-movement artist, teacher and cultural program director to insights gained during my doctoral studies to my application of the findings in subsequent participatory practice-based work. By doing so, I hope to stimulate us to consider the questions of what is the relevance of Kajian Budaya to our vocations in various fields? How might we make use of Kajian Budaya as praxis? Also, how can Kajian Budaya foster cultural creativity for the well-being of the earth and humanity?